Rancang Bangun E-Learning Pelajaran Produktif Multimedia Dan Pemasaran Pada Smk Karsa Mulya Kota Palangka Raya - Rif’an, Muhammad; Sylviana, Felicia; Ronaldo, Deddy (Universitas Palangka Raya, 2022)
The Electronic E-learning System for Productive Multimedia and Marketing Lessons at Karsa Mulya Vocational High School, Palangkaraya City, was built for convenience for teachers and students who during this time the learning process is always limited when studying in the room. In the process of designing an E-learning system for productive lessons in Multimedia and Marketing at SMK Karsa Mulya, Palangkaraya City, using the Waterfall Method according to Sommerville (2011: 29-30) which is divided into several stages, namely Analysis and definition of needs, system design and software, implementation and unit testing, system integration and testing, operation and maintenance. In the analysis and design stage the writer conducted a survey, interview and discussion with the school to find options and solutions for what features would be designed next and this analysis stage also made a flowchart, then used the programming language THML, PHP, CSS, Bootstrap, JavaScript and MySQL as the database creation. Then implemented into an E-learning website, which is carried out in the testing phase using a Blackbox. From the results of research that has been carried out by the author implementing the results of this study in the E-learning system of Productive Multimedia and Marketing lessons at SMK Karsa Mulya, Palangka Raya city. The output produced by this system is in accordance with the expected criteria and objectives, obtained an accuracy of 72.7% with a system error value of 27.2% in testing system results.